2015
DOI: 10.1371/journal.pone.0129865
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy to Improve the Therapeutic Efficacy of Gemcitabine for Non-Small Cell Lung Cancer by the Tumor-Penetrating Peptide iRGD

Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, comprising approximately 75–80% of all lung cancers. Gemcitabine is an approved chemotherapy drug for NSCLC. The objective of this study was to develop a novel strategy to improve the therapeutic efficacy of Gemcitabine for NSCLC by the co-administered iRGD peptide. We showed that the rates of positive expression of αvβ3, αvβ5 and NRP-1 in the A549 cell line were 68.5%, 35.3% and 94.5%, respectively. The amount of Evans Blue accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Treatment comprising a combination of GEM and iRGD was applied, which inhibited the growth of tumors, which were not sensitive to the same dose of GEM alone. Apoptotic cells in the tumor tissues were detected using a TUNEL assay and the statistical analysis revealed that the highest apoptotic index was for the groups treated with the GEM/iRGD combination (38).…”
Section: Irgd For Tumor Diagnosis and Treatmentmentioning
confidence: 99%
“…Treatment comprising a combination of GEM and iRGD was applied, which inhibited the growth of tumors, which were not sensitive to the same dose of GEM alone. Apoptotic cells in the tumor tissues were detected using a TUNEL assay and the statistical analysis revealed that the highest apoptotic index was for the groups treated with the GEM/iRGD combination (38).…”
Section: Irgd For Tumor Diagnosis and Treatmentmentioning
confidence: 99%
“…In a hepatocarcinoma xenograft model, utilizing the same mouse strain as Sugahara et al, Schmithals et al reported that co-administration of iRGD enhanced the penetration of DOX into tumor tissue as well as reduced tumor size as compared to DOX alone (Schmithals et al, 2015; Sugahara et al, 2010). Utilizing a different chemotherapeutic, Zhang et al reported that in an A549 xenograft model of non-small cell lung cancer, co-administration of iRGD along with gemcitabine lead to increased penetrance of drug to the tumor and decreased tumor volume over the treatment period of 30 days (Zhang et al, 2015). Finally, Lao et al reported that a thymosin alpha 1-iRGD conjugated form increased apoptosis of MCF-7 cells and decreased tumor volume over an 11 day treatment period when compared to thymosin alpha 1 alone (Lao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common cause of mortality in the world with an increasing incidence . The diagnosis is often made until reaching advanced‐stage, thus probably resulting in metastasis and a low survival rate of patients . Metastasis is a multistep process including local invasion, intravasation, extravasation, and colonization by which tumor cells disseminate from their primary site and form secondary tumors at a distant site .…”
Section: Introductionmentioning
confidence: 99%